Analysis Of Service Quality And Healthy Food Healthy Food Product Quality Towards Customer Satisfaction At Ayam Keprabon Gading Serpong Restaurant - Yanah, Ani; Tanu, Barbie Valerina; Natalie, Lytiana (Corespub, 2025)
This study aims to analyze the impact of service quality and healthy food product quality on customer satisfaction at Ayam Keprabon Restaurant, Gading Serpong. Using a qualitative approach, data were collected through observations and interviews with four customers of the restaurant. The findings indicate that high-quality products and excellent service significantly influence customer satisfaction.